Pilot study of a novel educational programme for 11–16 year olds with type 1 diabetes mellitus: the KICk-OFF course. Issue 11 (1st August 2008) - Waller, H; Eiser, C; Knowles, J; Rogers, N; Wharmby, S; Heller, S; Hall, C; Greenhalgh, S; Tinklin, T; Metcalfe, C; Millard, E; Parkin, V; et al.
Abstract : Aims: To pilot an educational programme (KICk-OFF) for children and adolescents with type 1 diabetes mellitus (DM). Evaluation included (i) independent assessment of curriculum quality, (ii) acceptability to families and (iii) possible impact on standardised outcome measures (HbA1c, body mass index (BMI), diary reports of hypoglycaemia, quality of life (QoL)). Methods: 48 children aged 11–16 years (mean age 13.60 (SD 1.36) years) were recruited from three UK centres. Six 5-day outpatient courses on carbohydrate counting and insulin dose adjustment were held. Semi-structured interviews were conducted with children and parents before and after the course. Glycaemic control (HbA1c), BMI and frequency of hypoglycaemia were assessed before the course and at 3 and 6 months after intervention. QoL was assessed before the course and at 2 weeks, 3 and 6 months. Results: Educational evaluation indicated the course format was appropriate and consistent. Parent and child interviews suggested that pre-course expectations were largely met. There were no changes in HbA1c, BMI or episodes of hypoglycaemia, but children and parents reported improved QoL (p<0.05). Conclusions: KICk-OFF was well-received by children and parents and was associated with improved QoL. In this small pilot study, glycaemic control did not change but findings justify conducting a future randomised controlled trial involving a revised curriculum, a larger study population including a control group and longer follow-up.